Is Spectral-Domain Optical Coherence Tomography Essential for Flexible Treatment Regimens with Ranibizumab for Neovascular Age-Related Macular Degeneration? - Abdullah Ozkaya; Zeynep Alkin; Hande Mefkure Ozkaya; Alper Agca; Engin Bilge Ozgurhan; Yalcin Karakucuk; Ahmet Taylan Yazici; Ahmet Demirok (Journal of Ophthalmology)
Purpose. To evaluate the ability of spectral-domain optical coherence tomography to detect subtle amounts of retinal fluid when the choroidal neovascularization is detected as inactive via time-domain optical coherence tomography and clinical examination in neovascular age-related macular degeneration (nAMD) patients. Methods. Forty-nine eyes of 49 patients with nAMD after ranibizumab treatment were included in this cross-sectional, prospective study. All patients were imaged with TD-OCT and SD-OCT at the same visit one month after a ranibizumab injection. The presence of subretinal, intraretinal, and subretinal pigment epithelium fluid (subRPE) in SD-OCT was evaluated; also mean central retinal thickness (CRT) and the rate of vitreoretinal surface disorders detected via the two devices were evaluated. Results. The mean CRT via TD-OCT and SD-OCT was 218.1±51.3 and 325.7±78.8 microns. Sixteen patients (32.6%) showed any kind of retinal fluid via SD-OCT. In detail, 8 patients (16.3%) showed subretinal fluid, 10 patients (20.4%) showed intraretinal fluid, and 3 patients (6.1%) showed SubRPE fluid. The ability of detecting vitreoretinal surface disorders was comparable between the two devices, except vitreomacular traction. Conclusion. SD-OCT is essential for the nAMD patients who are on an as-needed treatment regimen with ranibizumab. Only TD-OCT and clinical examination may cause insufficient treatment in this group of patients.